Functional evaluation of bilateral arthroereisis of subtalar joint and simultaneous gastrocnemius lengthening in symptomatic flexible flatfoot in children - Zafer Atbasi (Medicine Science, 2020)
The aim of this study was to report the radiological and pedobarographic results of 10 childrens 20 feet with symptomatic flexible flat foot, who were treated with gastrocnemius lengthening with arthroereisis of subtalar joint. A total of 10 childrens 20 feet (5 boys and 5 girls between 9-14-year-old) with painful feet due to the flatfoot were treated in our clinic between August 2016 and December 2018. Bilateral gastrocnemius lengthening and arthroereisis of subtalar joint was performed simultaneously. Radiological evaluation was performed by measuring calcaneal pitch angle and Mearys talusfirst metatarsal angles, pedobarographic evaluation by static and dynamic plantar heel and forefoot pressure data. The mean calcaneal pitch angle increased from 8° ± 0.93° preoperatively to 16.5° ± 1.14° postoperatively, and the mean Mearys talus-first metatarsal angle decreased from 7.5° ± 1.14°preoperatively to 0.5° ± 0.51° postoperatively. The mean heel peak pressure and the forefoot peak pressure ascended from 11.5 ± 1.14 (N/cm2) and 10.5 ± 1.14 (N/cm2) preoperatively to 17.5 ± 1.14 (N/cm2) and 15.5 ± 1.14 (N/cm2) postoperatively, respectively. Clinical evaluation revealed that 9 patient had painful feet, while 1 patient had discomfort since the implant had been inserted.Arthroereisis of subtalar joint with simultaneous gastrocnemius lengthening provides painful feet and seems to be an effective, simple and safe solution for symptomatic flexible flatfoot in pediatric patients. [Med-Science 2020; 9(1.000): 180-5]